2018
DOI: 10.1177/0883073818811234
|View full text |Cite
|
Sign up to set email alerts
|

Children Born With Congenital Zika Syndrome Display Atypical Gross Motor Development and a Higher Risk for Cerebral Palsy

Abstract: Importance: Congenital Zika syndrome virus infection is said to interfere in children's development. Objective: evaluate gross motor trajectories and the frequency of cerebral palsy in children with congenital Zika syndrome. Design: Cohort study applying the Alberta Infant Motor Scale (AIMS) and the Bayley III Scales in infants from 6 to 18 months of age. Setting: The SARAH network, Rio de Janeiro. Participants: Thirty-nine infants whose diagnoses were established through clinical history, serology tests, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
78
0
12

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(93 citation statements)
references
References 21 publications
2
78
0
12
Order By: Relevance
“…The resulting neurologic phenotype is characterized by hypertonicity, clonus, hyperreflexia, abnormal movements, spasticity, contractures, seizures, and cognitive impairment. 3,4,6…”
mentioning
confidence: 99%
“…The resulting neurologic phenotype is characterized by hypertonicity, clonus, hyperreflexia, abnormal movements, spasticity, contractures, seizures, and cognitive impairment. 3,4,6…”
mentioning
confidence: 99%
“…Importantly, there are now follow-up studies showing the effects from ZIKV-associated brain malformations or subtler damages. Such studies in infants with CZS confirmed strong neurological disabilities, in particular ocular and motor impairment, as well as epileptic manifestation [48,[55][56][57][58][59][60]. A study assessed over 1400 children of at least 1 year of age born from ZIKV-infected mothers and showed important rates of neurodevelopmental defects (up to 14% with seizure or, neurodevelopmental delays) [61].…”
Section: Congenital and Pediatric Arboviral Infections And Neurodevelmentioning
confidence: 85%
“…The evidence on CZS that was emerging at the time of this study highlighted the similarities of the physical presentation of CZS to those of CP. More recent literature has further described the overlapping between CZS and CP [35][36][37]. The review of the literature and findings of the social and economic impact study also suggested that there are similarities between CP and CZS, particularly in terms of needs and unmet needs of the caregiver.…”
Section: C)mentioning
confidence: 96%